Motivational Interactions: a client-centred engagement strategy in Australian accident compensation schemes. (12th November 2014) - Papagiannis, Arthur
Abstract : Motivational interactions is based on the foundations of "Motivational interviewing" and the "Transtheoretical Model of Behaviour Change", Which is widely recognised as an important engagement strategy for people working in a case management capacity- working with a range of injured client/worker needs pertaining to resistance, ambivalence to change, motivation, development and return to work. The quality of the working relationship between the worker and client is said to be a significant predictor of outcomes for a client. Evidence has indicated that a collaborative positive client centred engagement that is responsive to the change process of individuals is a reliable indicator of outcomes in a range of mental health, psychosocial and physical injury issues e.g. stress, depression, anxiety, physical injury, disability, with positive relationships being correlated with better Return to work/Life outcomes.